2003
DOI: 10.1002/ajmg.c.20011
|View full text |Cite
|
Sign up to set email alerts
|

Studies of offspring of parents with bipolar disorder

Abstract: Children and adolescents who are the biological offspring of individuals with bipolar disorder (BD) (bipolar offspring) represent a population rich in potential for revealing important aspects in the development of BD. Multiple cross-sectional assessments of psychopathology in bipolar offspring have confirmed high incidences of BD, as well as mood and behavioral disorders, and other psychopathology in this population. Longitudinal studies of offspring have begun to shed light on precursors of BD development. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
1
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 76 publications
(74 reference statements)
6
52
1
5
Order By: Relevance
“…In adults, the rates are around 5 to 10%, suggesting a larger genetic component in the early-onset form of BD. [42][43][44] In naturalistic studies of BD among children and adolescents, the recovery rates are high (70 to 100%), but the recurrence rate in 2 to 5 years is up to 80%. [45][46][47] Moreover, most of the time these patients experienced subsyndromal and syndromal mood symptomatology and frequent mood fluctuations, as reported in the Course and Outcome of Bipolar Youth (COBY, n=263) 2-year followup study.…”
Section: Epidemiologymentioning
confidence: 99%
“…In adults, the rates are around 5 to 10%, suggesting a larger genetic component in the early-onset form of BD. [42][43][44] In naturalistic studies of BD among children and adolescents, the recovery rates are high (70 to 100%), but the recurrence rate in 2 to 5 years is up to 80%. [45][46][47] Moreover, most of the time these patients experienced subsyndromal and syndromal mood symptomatology and frequent mood fluctuations, as reported in the Course and Outcome of Bipolar Youth (COBY, n=263) 2-year followup study.…”
Section: Epidemiologymentioning
confidence: 99%
“…It is expected that within families, endophenotype and the specifi c diagnosis co-segregate and the endophenotype is found in non-affected family members at a higher rate than in the general population. Concerning the prevalence of BD in families, it is well known that the offspring of BD parents are at a four times higher risk (Chang et al 2003 ), while fi rst-degree relative are at a 10-to-20-fold higher risk to develop BD (Glahn et al 2004 ;Smoller and Finn 2003 ).…”
Section: The Neurocognitive Deficit As An Endophenotype For Bdmentioning
confidence: 99%
“…6 Regarding specific psychiatric diagnoses besides mood disorders, attention-deficit hyperactivity disorder (ADHD) or significant behavioral or attentional problems have been reported in approximately 27% of bipolar offspring studied. 7 In children with strong family history of BD, the diagnosis of ADHD can be the first sign of a BD. 8 More recently, Henin et al 9 documented a higher prevalence of anxiety disorders in bipolar offspring (36%) compared to rates detected in children of psychiatrically healthy parents (14%).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are concordant with those suggesting that an anxiety disorder might be an alternative pathway for the further development of BD. 7 Hirshfeld-Becker et al 10 studied a sample of children with a mean age of 6.8 years and described significantly higher rates of disruptive behavior and anxiety disorders in bipolar offspring than in offspring of both parents with panic or major depression and parents with neither mood nor anxiety disorders. Wals et al found that daughters of bipolar parents obtained significantly higher scores on the following CBCL scales: Total Problems, Internalizing, Externalizing, Somatic Complaints, Anxious/Depressed, Social problems, Delinquent Behavior and Aggressive Behavior; and sons of bipolar parents obtained significantly higher scores on the Total Problems, Externalizing, Thought Problems and Aggressive Behavior scales than the normative sample.…”
Section: Introductionmentioning
confidence: 99%